Assessment of causal associations between obesity and peripheral artery disease: a bidirectional Mendelian randomization study - Huang, Xi-wei; Pang, Shu-wen; Zhang, Tao; Huang, Chuang-wei (Frontiers in Cardiovascular Medicine, 2024)
Background: Several observational studies have documented a potential link between obesity and peripheral artery disease (PAD), although conflicting findings exist. The causal relationship between obesity and PAD continues to be a subject of ongoing debate in the medical community. Objectives: In this study, we employed a bidirectional Mendelian randomization (MR) analysis to explore the potential causal relationship between obesity and the risk of PAD. Methods: To investigate these causal relationships, we conducted bidirectional MR analysis using publicly available genome-wide association study (GWAS) data. Effect estimates were calculated using the random-effects inverse variance-weighted (IVW) method. Results: We identified eight independent single nucleotide polymorphisms (SNPs) associated with obesity in 218,735 samples involving 16,380,465 SNPs, all of which met the genome-wide significance threshold (p<5×10⁻⁸). The IVW analysis indicates a significant positive association between genetic obesity and multiple datasets with PAD as the outcome: Queue-1 (GWAS ID: finn-b-I9_PAD) (OR=1.138, 95%CI: 1.027-1.261, p=0.013), Queue-2 (GWAS ID: bbj-a-144) (OR=1.190, 95%CI: 1.019-1.390, p=0.028), Queue-3 (GWAS ID: ebi-a-GCST90018670) (OR=1.174, 95%CI: 1.014-1.360, p=0.032), and Queue-4 (GWAS ID: ebi-a-GCST90018890) (OR=1.194, 95%CI: 1.099-1.296, p<0.001). However, we did not observe a significant genetic-level association between obesity and PAD for Queue-5 (GWAS ID: ukb-d-I9_PAD) (OR=1.001, 95%CI: 1.000-1.002, p=0.071). Furthermore, we conducted a reverse causal MR analysis to explore the potential reverse causal relationship between obesity and PAD. This comprehensive analysis did not provide evidence of a reverse causal association between these two factors. Conclusions: In summary, our study offers genetic evidence suggesting a possible causal link between obesity and PAD. While we did not find evidence supporting the "obesity paradox", prudent weight management remains crucial, as lower weight does not necessarily guarantee better outcomes. As with any study, caution is required in interpreting the findings. Further research is essential to assess the clinical relevance of weight in preventing PAD, which could inform the development of more precise intervention strategies.